Facilitating Adult Learning During Traumatic and Turbulent Times - Patricia J Higgins (Adult Education Research Conference, 2025)
The purpose of this exploratory case study is to consider how a mindfulness approach to teaching adults could impact adult learner persistence, engagement, and well-being during traumatic times.
Keywords: Trauma; Mindfulness; Adult Education; Educational Psychology